2023
DOI: 10.3389/fpsyg.2023.1168032
|View full text |Cite
|
Sign up to set email alerts
|

The influence of student factors on students’ achievement in the Trends in International Mathematics and Science Study in Abu Dhabi Emirate Schools

Abstract: IntroductionThis study aimed to investigate student factors affecting performance in mathematics in Abu Dhabi schools in the United Arab Emirates.MethodWe used the secondary data from the Trends in International Mathematics and Science Study (TIMSS) 2015, which included 4,838 eighth-grade students from 156 schools in Abu Dhabi.ResultThe data from the student questionnaire in TIMSS 2015 were subjected to principal component analysis (PCA). The 39 questions were reduced to five factors generated from the student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…The notable disparities in mean scores between the experimental and control cohorts following the intervention highlight the substantial effect of the ChatGPT implementation on student attainment. These outcomes align with prior investigations demonstrating the efficacy of AI chatbots in augmenting students' educational achievements across diverse scenarios [53]. The findings imply that ChatGPT might be especially advantageous in nurturing advanced cognitive skills, such as application and reasoning, as evidenced by the elevated mean scores in these categories for the experimental group [54,55].…”
Section: A Questionsupporting
confidence: 86%
“…The notable disparities in mean scores between the experimental and control cohorts following the intervention highlight the substantial effect of the ChatGPT implementation on student attainment. These outcomes align with prior investigations demonstrating the efficacy of AI chatbots in augmenting students' educational achievements across diverse scenarios [53]. The findings imply that ChatGPT might be especially advantageous in nurturing advanced cognitive skills, such as application and reasoning, as evidenced by the elevated mean scores in these categories for the experimental group [54,55].…”
Section: A Questionsupporting
confidence: 86%
“…Soares’ [ 28 ] study indicated that e-learning models had a high impact on the development of scientific passion and digital culture [ 28 ]. Additionally, Brik and Al-Jariwi’s study concluded that there is a statistically significant correlation between psychological distance in its various dimensions and the total degree of academic passion [ 29 ]. Furthermore, Greenberger’s study [ 30 ] examined the relationship between academic passion (consensual and compulsive) and face-to-face or online teaching and found that 95% of the study sample who studied online were enthusiastic about e-learning and had academic passion for online learning [ 30 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, these works have delved into examining the diverse impacts of emotions and the dual model of passion on distance learning experiences. On the basis of the preceding discussions, it can be deduced that the most noteworthy aspect of this particular study lies in its assessment of students’ learning emotions and the organization and management of knowledge, which can serve as indicators of the distance learning system’s quality [ 5 , 27 , 29 , 32 , 34 , 35 , 36 ]. Furthermore, this study sheds light on learners within distance learning contexts, encompassing their levels of satisfaction, patterns of interaction, and strategies for organizing and managing cognitive processes in digital environments.…”
Section: Literature Reviewmentioning
confidence: 99%